Electrospun Chitosan–Polyvinyl Alcohol Nanofiber Dressings Loaded with Bioactive Ursolic Acid Promoting Diabetic Wound Healing - Hongyu Lv; Meng Zhao; Yiran Li; Kun Li; Shaojuan Chen; Wenwen Zhao; Shaohua Wu; Yantao Han (Nanomaterials, 2022)
The design and development of novel dressing materials are urgently required for the treatment of chronic wounds caused by diabetic ulcers in clinics. In this study, ursolic acid (UA) extracted from Chinese herbal plants was encapsulated into electrospun nanofibers made from a blend of chitosan (CS) and polyvinyl alcohol (PVA) to generate innovative CS-PVA-UA dressings for diabetic wound treatment. The as-prepared CS-PVA-UA nanofiber mats exhibited randomly aligned fiber morphology with the mean fiber diameters in the range of 100–200 nm, possessing great morphological resemblance to the collagen fibrils which exist in the native skin extracellular matrix (ECM). In addition, the CS-PVA-UA nanofiber mats were found to possess good surface hydrophilicity and wettability, and sustained UA release behavior. The in vitro biological tests showed that the high concentration of UA could lead to slight cytotoxicity. It was also found that the CS-PVA-UA nanofiber dressings could significantly reduce the M1 phenotypic transition of macrophages that was even stimulated by lipopolysaccharide (LPS) and could effectively restore the M2 polarization of macrophages to shorten the inflammatory period. Moreover, the appropriate introduction of UA into CS-PVA nanofibers decreased the release levels of TNF-α and IL-6 inflammatory factors, and suppressed oxidative stress responses by reducing the generation of reactive oxygen species (ROS) as well. The results from mouse hepatic hemorrhage displayed that CS-PVA-UA nanofiber dressing possessed excellent hemostatic performance. The in vivo animal experiments displayed that the CS-PVA-UA nanofiber dressing could improve the closure rate, and also promote the revascularization and re-epithelization, as well as the deposition and remodeling of collagen matrix and the regeneration of hair follicles for diabetic wounds. Specifically, the mean contraction rate of diabetic wounds using CS-PVA-UA nanofiber dressing could reach 99.8% after 18 days of treatment. In summary, our present study offers a promising nanofibrous dressing candidate with multiple biological functions, including anti-inflammation, antioxidation, pro-angiogenesis, and hemostasis functions, for the treatment of hard-to-heal diabetic wounds.